1986
DOI: 10.1128/mmbr.50.4.381-400.1986
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Borrelia species.

Abstract: TABLE 1. Borrelia species associated with diseases of humans and domestic animals % DNA Borrelia Sp.a Disease homology with Arthropod vector' Geographic distribution of disease B. hermsiib B. hermsii New World tick-borne 100 0. hermsi Western United States and Canada relapsing fever B. turicatae New World tick-borne 86 0. turicata Southwestern United States and relapsing fever northern Mexico B. parkeri New World tick-borne 77 0. parkeri Western United States and Baja relapsing fever California B. mazzottii Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
211
1
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(223 citation statements)
references
References 106 publications
2
211
1
9
Order By: Relevance
“…Similar and probably equivalent borrelial structures (so-called blebs, gemmae, spheroplasts, L-forms) were described even before this by different researchers (2)(3)(4)(5). Outer surface blebs and gemmae containing granular material were observed in borreliae as long as 50 years ago (6). These structures were associated with spirochetal cells undergoing degenerative changes in a hostile environment (ambient changes, antibiotic treatment, host immune defence activity -antibodies and complement, aging of in vitro borrelial culture etc.…”
mentioning
confidence: 61%
“…Similar and probably equivalent borrelial structures (so-called blebs, gemmae, spheroplasts, L-forms) were described even before this by different researchers (2)(3)(4)(5). Outer surface blebs and gemmae containing granular material were observed in borreliae as long as 50 years ago (6). These structures were associated with spirochetal cells undergoing degenerative changes in a hostile environment (ambient changes, antibiotic treatment, host immune defence activity -antibodies and complement, aging of in vitro borrelial culture etc.…”
mentioning
confidence: 61%
“…The louse-borne relapsing fever (also known as urban or epidemic RF) is caused by Borrelia recurrentis, and is transmitted by the body louse Pediculus humanus humanus. Historically, massive outbreaks have occurred in Eurasia and Africa, especially during wartime, when people were highly parasitized with body lice (Barbour & Hayes, 1986). Currently, the disease is found only in Ethiopia and neighbouring countries (Raoult & Roux, 1999).…”
mentioning
confidence: 99%
“…When more than seven flagella were present in a bacterium, the flagellar filaments can pile up in what appears like a bundle of multiple small flagellar ribbons (Kudryashev et al, 2009). We and others have also noted the presence of an additional surface layer surrounding the outer membrane of Borrelia that we first called amorphous slime layer, based on previous statements (Hovind-Hougen, 1984;Barbour and Hayes, 1986). Subsequently, the disappearance of this layer upon surface proteolysis using proteinase K demonstrated that it is composed of outer-surface proteins (Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 77%